Childhood obesity and in‐hospital asthma resource utilization. Issue 3 (2nd December 2014) - Bettenhausen, Jessica; Puls, Henry; Queen, Mary Ann; Peacock, Christina; Burrus, Stephanie; Miller, Christopher; Daly, Ashley; Colvin, Jeffrey D.
<x xml:space="preserve">Abstract</x> OBJECTIVE To examine the relationship between pediatric obesity and inpatient length of stay (LOS), resource utilization, readmission rates, and total billed charges for in‐hospital status asthmaticus. DESIGN/METHODS We conducted a cross‐sectional study of patients 5 to 17 years old hospitalized with status asthmaticus to 1 free‐standing children's hospital system over 12 months. Only hospitalized patients initially treated in the hospital's emergency department were included to ensure all therapies/charges were examined. Patients with complex chronic conditions, pneumonia, or lacking recorded body mass index (BMI) were excluded. The primary exposure was BMI percentile for age. The primary outcome was LOS (in hours). Secondary outcomes were 90‐day readmission rate, billed charges, and resource utilization: number of albuterol treatments, chest radiographs, intravenous fluids, intravenous or intramuscular steroids, and intensive care unit admission. Bivariate, adjusted Poisson and logistic regression model analyses were performed. RESULTS Five hundred eighteen patients met inclusion criteria. Most had a normal BMI (59.7%); 36.7% were overweight or obese. LOS, readmissions, and resource utilization outcomes were not associated with BMI category on bivariate analyses. After adjustment for demographic/clinical characteristics, LOS decreased by 2% for each decile increase in BMI percentile for age. BMI percentile for age was not associated with billed charges, readmissions, or other measures of resource utilization. CONCLUSIONS Although BMI decile for age is inversely associated with LOS for in‐hospital pediatric status asthmaticus, the effect likely is not clinically meaningful. Journal of Hospital Medicine 2015;10:160–164. © 2014 Society of Hospital Medicine